Auditor Capability on the Effectiveness of Red Flags in Detecting Fraud - Magdalena Judika Br Siringoringo; Christnova Hasugian; Sri Ida Royani Simanjuntak; Manatap Berliana Lumbangaol; Markus Doddy Simanjuntak (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Fraud detection remains a major challenge in the auditing field, as fraudulent activities are often concealed and difficult to identify directly. Red flags, or early warning indicators, are commonly used as tools to assist in detecting potential fraud. This study aims to analyze the influence of tenure, education level, experience in detecting fraud, and training in fraud detection on the effectiveness of red flags in identifying fraud. A quantitative approach was employed by distributing questionnaires to 42 auditors from 7 Public Accounting Firms (PAFs) located in Medan City. Data were analyzed using multiple linear regression with the aid of SPSS software. The results show that tenure does not have a significant effect on the effectiveness of red flags. However, education level, experience in detecting fraud, and training in fraud detection each have a positive and significant influence on the effectiveness of red flags in uncovering fraudulent activities. These findings suggest that enhancing auditors' competencies—particularly through education, relevant experience, and training—plays a crucial role in optimizing the use of red flags as early detection tools in fraud examination.